Synthesis and Characterization of Schiff Base from 4,4-Diaminodiphenyl Ether and Vanillin and its Interaction with Cu2+ Metal Ion - Nurlisa Hidayati; Erika Dhamayanti; Desnelli Desnelli; Muhammad Said; Nova Yuliasari; Umi Nurlailia (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2024)
The Schiff base has synthesized from the reaction between 4,4-diaminodiphenyl ether and vanillin. The resulting Schiff base acts as a ligand and interacts with Cu2+ metal ions to form a complex compound. The Schiff base was analyzed using UV-visible and FT-IR spectroscopy, as well as X-ray diffraction (XRD). The stability of the Schiff base under different pH conditions was investigated, along with the interference effects of Cd2+ and Zn2+ ions on the formation of Schiff base complexes with Cu2+. The formation of a yellow solid crystal indicated the successful synthesis of the Schiff base. The appearance of maximum absorption at 250 nm on the UV-Vis spectra signifies the electronic transition from Ï€ to Ï€*. Absorption spectra at 1600 cm-1 indicate the presence of an azomethine group. The diffraction pattern showed a sharp peak at an angle of 2Î¸= 19.301Â°, 51.04Â° for the Schiff base 4,4-diamino diphenyl ether-vanillin. Schiff base compounds exhibit the highest stability at pH 5, where the C=N double bond formed is more stable than other pH. Schiff base ligands form complexes with Cu2+ metal ions, characterized by absorption in the charge transfer region (LMCT) at Î» 400 nm and the d-d transition at Î» 630 nm. The presence of CdÂ²âº and ZnÂ²âº metal ions shifting absorption of the Schiff Base-CuÂ²âº ligand complex towards shorter wavelengths (hypsochromic effect)